Análisis de lo fantástico y las transiciones femeninas en el cine de Roman Polanski: "Repulsión" (1965) y "El bebé de Rosemary" (1968) - Huapaya Villacampa, Maria Fernanda (2022)
The present work focuses on the study between the "fantastic" and the transits of the feminine imaginary in the cinema of the director Roman Polanski, taking as objects of analysis the films Repulsion (1965), and Rosemary's Baby (1968). In both, the development of fantastic fiction highlights the experiences of the protagonists' hallucination while they are in a liminal situation. One of them, the experience of isolation and erotic repression in a London apartment. The other, the process of maternal gestation in an environment that fills her with concerns. They, in their liminal transit, face visions or hallucinations that could be explained as products of a mental disorder or as manifestations of something supernatural, which roots both films in the concept of the "fantastic" proposed by theorist Tzvetan Todorov